Effect of Hen`s Age on the Level of Cystatin in the Chicken Egg White - Trziszka, Tadeusz; Saleh, Yousif; Kopeae, Wieslaw; Siewinski, Maciej; Wesierska, Ewelina (International Journal of Poultry Science, 2004)
Cystatins, protein-type cysteine proteinase inhibitors are widely distributed in animals and plants. It is generally assumed that these inhibitors are involved in the regulation of physiological and pathological processes caused by cysteine proteinases Cystatins. The study aimed to isolate and characterize the cystatin from various chicken in different ages between 20-80 weeks. We used acid treatment, affinity chromatography Sepharose-Papain-4B, and desalting G-25 column, followed gel chromatography G-100 column. We obtained that the chicken in age 50 weeks have a higher activity against papain and the yield of cystatin among the chicken in ages 20, 30, 40, 60, 65, 70 and 80 weeks. The purified cystatin was shown to be homogenous by polyacrylamide gel electrophoreses (SDS-PAGE) The molecular weight of first and second fractions were determined to be 40 000 and 13 000, respectively. The low molecular fraction was strongly inhibited papain (Ki = 0.0012 nM) and cathepsin B (Ki =2.554 nM).